An Analysis of Teacher Methods in Teaching English for Disabilities Students - Sri Rahayu Nengsi; Sitti Maryam Hamid; Awalia Aziz (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Teaching English to students with special needs there are several challenges faced by the teacher but with the methods used by the teacher such as the grammar-translation method, the direct method, the natural method, the audio-lingual method, the cognitive-code method, the communicative method, total physical response, discovery learning and media. This study uses descriptive qualitative method which aims to find out the method will use by a teacher in learning English to students with special needs at Sekolah Luar Biasa 1 Gowa. The researcher used observation and interview with only one teacher to collect the data. To analyze the data the researcher used notes from the observation and the interview. to find out the methods for teaching English in the classroom activities.; the data showed that teacher used discovery learning and media as method in the learning process. The implementation of this method makes the teacher provide about learning and make student learnt with fun. It is concluded that the teacher uses a method that can make students who have limitations with media that support their teaching better.